Physical performance profiles in Norwegian premier league female football: A descriptive study - Vagle, M.; Dalen-Lorentsen, T.; Moksnes, H.; Harøy, J.; Bjørneboe, J.; Andersen, T. E. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To map anthropometric and physical performance profiles in Norwegian premier league female football players.